Classification of in vitro genotoxicants using a novel multiplexed biomarker assay compared to the flow cytometric micronucleus test. (21st September 2017) - Wilde, Sabrina; Dambowsky, Miriam; Hempt, Claudia; Sutter, Andreas; Queisser, Nina
Abstract : Regulatory in vitro genotoxicity testing exhibits shortcomings in specificity and mode of action (MoA) information. Thus, the aim of this work was to evaluate the performance of the novel MultiFlow ® assay composed of mechanistic biomarkers quantified in TK6 cells after treatment (4 and 24 hr): γH2AX (DNA double strand breaks), phosphorylated H3 (mitotic cells), translocated p53 (genotoxicity), and cleaved PARP1 (apoptosis). A reference dataset of 31 compounds with well‐established MoA was studied using the MicroFlow ® micronucleus assay. A positive call was raised following the earlier published criteria from Litron Laboratories. In the light of our data, these evaluation criteria should probably be adjusted since only 8/11 (73%) nongenotoxicants and 18/20 (90%) genotoxicants were correctly identified. Moreover, there is a need for new in vitro tools to delineate the predominant MoA as in the MicroFlow ® assay only 5/9 (56%) aneugens and 4/11 (36%) clastogens were correctly classified. In contrast, the MultiFlow ® assay provides more in‐depth information about the MoA and therefore reliably discriminates clastogens, aneugens, and nongenotoxicants. By using a lab‐specific, practical threshold for the aforementioned biomarkers, 10/11 (91%) nongenotoxicants and 19/20 genotoxicants (95%), 9/11 (82%) clastogens, and 8/9 (89%) aneugens were correctly categorized, suggesting a clear improvement over the MicroFlow ® . Furthermore, the MultiFlow markers were benchmarked against established methods to assess the validity of the data. Altogether, these findings demonstrated good agreement between the MultiFlow ® assay and the benchmarking methods. Finally, p21 may improve class discrimination given the correct identification of 4/4 (100%) aneugens and 2/5 (40%) clastogens. Environ. Mol. Mutagen. 58:662–677, 2017. © 2017 Wiley Periodicals, Inc.